2018
DOI: 10.3892/or.2018.6366
|View full text |Cite
|
Sign up to set email alerts
|

let-7d-3p is associated with apoptosis and response to neoadjuvant chemotherapy in ovarian cancer

Abstract: Altered expression of microRNAs contributes to the heterogeneous biological behavior of human malignancies and it may correlate with the clinical pathological features of patients. The let-7 microRNA family is frequently downregulated in human cancers and its aberrant expression may be a useful marker for prediction of the clinical response to therapy in patients. In the present study, we analyzed the expression of three members of the let-7 family (let-7a-3p, let-7d-3p and let-7f), which remains largely uncha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Thus far, there has been no such report to show the protective effect of Let-7d-3p in this context and it has not even been characterized in any cardiovascular diseases. In ovarian cancer, the inhibition of Let-7d-3p using antagomiRs showed a significant decreased in cell proliferation and activated apoptosis in ovarian cancer cells [32]. These results seem in line with our finding that Let-7d-3p mimic enhanced cell viability and reduced apoptosis.…”
Section: Discussionsupporting
confidence: 89%
“…Thus far, there has been no such report to show the protective effect of Let-7d-3p in this context and it has not even been characterized in any cardiovascular diseases. In ovarian cancer, the inhibition of Let-7d-3p using antagomiRs showed a significant decreased in cell proliferation and activated apoptosis in ovarian cancer cells [32]. These results seem in line with our finding that Let-7d-3p mimic enhanced cell viability and reduced apoptosis.…”
Section: Discussionsupporting
confidence: 89%
“…Studies have shown that one-third of the human genome can be regulated by miRNAs [55], which play an important regulatory role in cancers and metabolic diseases. Most miRNAs in the ceRNA network have been found to be closely related Journal of Diabetes Research to cancers [56][57][58][59]. In addition, Rohm et al [60] found that the expression of hsa-let-7d-5p was increased in the experimental group compared with the undifferentiated control group during adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The increased expression of let-7d-3p was correlated with a positive response to platinum/paclitaxel treatment in ovarian cancer patients. Additionally, let-7d-5p miRNA was reported to rescue ovarian cancer cells apoptosis and chemosensitivity by modulating the p53 pathway via high a mobility group 1 (HMGA1) [119].…”
Section: Indirect Cellular Processes That Affect Apoptosis Inductionmentioning
confidence: 99%